Bispectral index monitoring of the clinical effects of propofol closed-loop target-controlled infusion: Systematic review and meta-analysis of randomized controlled trials. Issue 4 (29th January 2021) - Wang, Danyang; Song, Zichen; Zhang, Chunlu; Chen, Peng
Abstract: Background: To investigate whether closed-loop systems under bispectral index anesthesia depth monitoring can reduce the intraoperative propofol dosage. Methods: All randomized controlled trials (RCTs) on reducing propofol dosage under closed-loop systems were collected, and the literature was screened out, the abstracts and full texts were carefully read, and the references were tracked, data extraction and quality evaluation were conducted on the included research, and the RevMan5.3 software was used for meta-analysis. The main results were propofol and the incidence of adverse reactions such as hypertensive hypotension and postoperative cognitive dysfunction. A total of 879 cases were included in 8 articles, including 450 occurrences in the closed-loop system group and 429 cases in the open-loop system group. Results: Compared with manual control, closed-loop systems under bispectral index anesthesia depth monitoring reduced the dose of propofol (MD: −0.62, 95% CI: −1.08–−0.16, P = .008), with heterogeneity ( I 2 = 80%). Closed-loop systems significantly reduced the incidence of abnormal blood pressure (MD: −0.02, 95%CI: −0.05–0.01, P = .15, I 2 = 74%) and postoperative cognitive dysfunction (MD: −0.08, 95% CI: −0.14 −0.01, P = .02, I 2 = 94%). Conclusion: Bispectral index monitoring of propofol closed-loop target-controlled infusion system can reduce the amount of propofol, reduce the incidence of adverse reactions such as hypertensive or hypotension and postoperative cognitive dysfunction.